Implementasi Supervisi Akademik Teknik Coaching dalam Meningkatkan Pembelajaran Mendalam: Studi Kualitatif di SD Negeri Pancurwening - Narwastujati Sepharibada Yudarasa; Pardimin Pardimin; Saryanto Saryanto (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to anlayze the implementation of academic supervision using coaching techniques in improving deep learning at SD Negeri Pancurwening. The research focuses on supervision planning, implementation of coaching-based supervision, utilization of feedback, and supporting and inhibiting factors. This research employed a descriptive qualitative approach. The subjects cocsisted of one principal and two teachers. Data were collected through in-depth interviews, classroom observations, and document analysis. Data validity was ensured through source and technique triangulation. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclussion drawing. The findings indicate that coaching-based academic supervision was implemented systematically through ore-observation, observation, and post-observation stages emphasizing partnership and reflective dialogue. Coaching encouraged teachers to reflect, identify instructional challenges, and independently design follow-up improvement plans. The utilization of supervision feedback positively contributed to improving teachers’ competence in implementing meaningful, conscious, and engaging deep learning. Supporting factors included the principal’s coaching competence and collaborative school culture, while time constraints and managerial workload became the main inhibiting factors. This study contributes to the development of a supervision model oriented toward teacher empowerment in elementary schools.